Medicaid recipients in intermediate care facilities for the mentally retarded - Burwell, Brian (CENTERS for MEDICARE & MEDICAID SERVICES, 1987)
In this study, we examined Medicaid utilization and expenditure patterns of Medicaid recipients in intermediate care facilities for the mentally retarded (ICF's/MR) in three States: California, Georgia, and Michigan. Data were obtained from uniform Medicaid data files (Tape-to-Tape project). Most recipients in ICF's/MR were nonelderly adults with severe or profound mental retardation who were in an ICF/MR for the entire year. The average annual cost of care ranged from $26,617 per recipient in Georgia to $36,128 per recipient in Michigan. The vast majority of recipients were low utilizers of other Medicaid services. Approximately one-third of the recipients were also covered by Medicare.